A key to genera of Iranian lady beetles (Coleoptera: Coccinellidae) and species of subfamilies Chilocorinae, Coccinellinae, Epilachinae and Microweiseinae - Abdolahi, R.; Nedvěd, Oldřich; Nozari, J. (Akadémiai Kiadó, 2017)
Although there are many literatures related to fauna of Iranian Coccinellidae, mostly they were faunistic reports without any appropriate key, even to the Iran subfam¬ilies. Many of Iranian lady beetle species are really rare and have been described since many years ago. For many species, particularly rare species, literatures are too old and not available in internet. Also for many species descriptions are not in English. Maybe that’s why there was not any key to Iranian lady beetles so far, even to subfamilies and tribes. For this purpose this paper is an attempt to provide a key to genera of Iranian lady beetles, besides species of the subfamilies Chilocorinae, Epilachinae Microweiseinae and Coccinellinae.
Keywords: Lady beetle; key; Iran